Schizophyllan Polysaccharide from Schizophyllum commune demonstrates antinociceptive effect on preclinical models of acute pain - Katherine Plautz; Gabriela Borgmann; Alessandra Betina Gastaldi; Gustavo Schuetzler Gomes Fernandes; Eduardo Manoel Pereira; Samira Dal-Toé de Prá; Nicole Dalonso; Débora Delwing-Dal Magro; Daniela Delwing-de Lima (ABCS Health Sciences)
Introduction: Twenty-five to 29% of the global population experiences pain that motivates seeking emergency services. Objective: To evaluate the effect of schizophyllan glucan polysaccharide (SPG), an isolated β-(1→3),(1→6) glucan polysaccharide of Schizophyllum commune, in acute pain and neuromuscular performance on pre-clinical models. Methods: Male adult Swiss mice (20-30g, 60 days) were acclimated for a week in groups of 7 per cage before the experiment. SPG was administered, intraperitoneally, at doses of 0.1, 1.0, 3.0, 5.0, 10.0, 30.0, and 100.0 mg/Kg for the writhing test, and 1.0, 10.0, and 30.0 mg/Kg for the formalin and Rotarod tests, respectively. Statistical analysis was performed using one-way ANOVA, followed by the Duncan post hoc test, respectively, as appropriate (p<0.05). Results: Regarding the abdominal writhing test, SPG doses of 1.0, 5.0, 10.0, 30.0, and 100.0 mg/Kg promoted a significant reduction in writing of, respectively, 90.6%, 86.6%, 83.0%, 86.6%, and 76.2%. In the formalin test, the dose of SPG 30 mg/Kg reduced phase II nociception time by 78.0%. Relevant sedation was observed only to SPG 100 mg/Kg in the Rotarod test. Conclusion: SPG showed significant analgesic effects on acute inflammatory pain without causing concomitant central nervous system depression.